Cultural Value Inheritancance of Cikondang Indigenous People in History Learning in Madrasah Aliyah Al-Hijrah - Yulianti, Iing (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
The local cultural values that were recently ignored are an essential issue to be highlighted in teaching history. This research focuses on the cultural values inheritance of Cikondang indigenous people, particularly among young people who are studying in Madrasah Aliyah Al-Hijrah Cikondang, through history education. The approach used in this study is a qualitative approach with ethnographic methods. The results show that the cultural values of the Cikondang society can be actualized and internalized in the lessons of history, including ecological wisdom, respect for history, cooperation culture, education wisdom, and economic wisdom. The teacher has made the community and the surrounding environment a source of learning. Students can match what is acceptable in the classroom with the reality of the environment. Internalization appears in the behavior and consciousness of the students toward the culture of values Cikondang who lived and actualized in everyday life. Thus the inheritance of local wisdom is significant in learning history so that students will know and understand the noble values contained in the culture. This indicates that school has a great potential as the vehicle for the inheritance of the cultural values proven by times.